Automatic Morpheme Segmentation for Russian: Can an Algorithm Re-place Experts? - Дмитрий Алексеевич Морозов; Тимур Александрович Гарипов; Ольга Николаевна Ляшевская; Светлана Олеговна Савчук; Борис Леонидович Иомдин; Анна Валерьевна Глазкова (Journal of Language and Education, 2024)
Introduction: Numerous algorithms have been proposed for the task of automatic morpheme segmentation of Russian words. Due to the differences in task formulation and datasets utilized, comparing the quality of these algorithms is challenging. It is unclear whether the errors in the models are due to the ineffectiveness of algorithms themselves or to errors and inconsistencies in the morpheme dictionaries. Thus, it remains uncertain whether any algorithm can be used to automatically expand the existing morpheme dictionaries.